Isolation and characterization of microsatellite loci in Sorbus porrigentiformis and cross‐amplification in S. aria and S. rupicola (Rosaceae)1. (14th February 2017) - Piñeiro, Rosalía; Karrman‐Bailey, Freja; Cowan, Robyn S.; Fay, Michael F.
Abstract : Premise of the study: Southwestern Britain is an emblematic hotspot of polyploid diversity of whitebeams ( Sorbus aria agg.; Rosaceae) with ca. 30 polyploid endemic species. The tetraploid S. porrigentiformis is postulated as one of the parents of most of these endemics, along with the sexual diploid S. aria s. str. and the tetraploid S. rupicola . Methods and Results: We isolated 16 nuclear microsatellite loci from S. porrigentiformis and characterized them on 45 trees representing the three putative parental species. Eleven loci were polymorphic, and eight of them exhibited species‐specific alleles. Allele numbers ranged from one to 11, and observed heterozygosity ranged from 0.40 to 1.00. The intraspecific levels of variation were very low, in agreement with the facultative apomictic reproduction hypothesized for this species. Conclusions: The species‐specific alleles will be useful for tracing the origin of the narrowly distributed Sorbus taxa. In addition, the assessment of diversity levels will help design a conservation strategy for the polyploid complex.